Vloga molitve v protestantski reformaciji: teološke in družbene spremembe v 16. stoletju - Mesarič, Violeta Vladimira (Edinost in dialog, 2024)
The prayer practice in the Protestant Reformation is rooted in a profound theological renewal, most notably highlighted by Martin Luter and Jean Calvin. The central theological idea of justification by faith significantly influenced forms of prayer and devotion in the daily lives of believers. Printed prayer books played a crucial role in spreading new theological views to the wider population. Additionally, prayer held a central place in household churches, where women, especially mothers, took on a key role in maintaining and spreading prayer practices. This article focuses on the key theological changes in the practice of prayer and their social impact, with a special emphasis on the role of women. It also examines the Reformation in the Slovenian context and the contributions of Primož Trubar and Jurij Dalmatin to the understanding and practice of prayer in the daily lives of Slovenian believers.